2019
DOI: 10.1007/s40273-019-00805-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Elderly Pneumococcal Vaccination in Presence of Higher-Valent Pneumococcal Conjugate Childhood Vaccination: Systematic Literature Review with Focus on Methods and Assumptions

Abstract: Background Previous systematic reviews concluded that pneumococcal vaccination in the elderly was cost effective. However, recently published economic evaluations state that it may not be cost effective when children are vaccinated with higher-valent pneumococcal conjugate vaccines. The literature suggests that the outcomes of vaccination in the elderly are strongly influenced by the vaccine effectiveness (VE) against the vaccine-type pneumococcal diseases (PD) and the impact of childhood vaccination on the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
0
18
0
1
Order By: Relevance
“…Of the four studies that evaluate the addition of PCV13 Adult to adult PPV23 (as was the case in Turkey), van Hoek and Miller (2016), 20 Blommaert et al (2016), 21 and Willem et al (2018) 22 found doing so to be cost-ineffective, while Stoecker et al (2016) 23 found it to be cost-effective only in the short run before herd effects fully set in. Treskova et al (2019) 18 conclude from this evidence that PCV13 Adult is not cost-effective in the presence of herd effects from PCV13 Pediatric.…”
Section: Literature On Economic Evaluation Of Pcv13 Adultmentioning
confidence: 85%
See 2 more Smart Citations
“…Of the four studies that evaluate the addition of PCV13 Adult to adult PPV23 (as was the case in Turkey), van Hoek and Miller (2016), 20 Blommaert et al (2016), 21 and Willem et al (2018) 22 found doing so to be cost-ineffective, while Stoecker et al (2016) 23 found it to be cost-effective only in the short run before herd effects fully set in. Treskova et al (2019) 18 conclude from this evidence that PCV13 Adult is not cost-effective in the presence of herd effects from PCV13 Pediatric.…”
Section: Literature On Economic Evaluation Of Pcv13 Adultmentioning
confidence: 85%
“…Dirmesropian et al (2015) 19 review pre-2015 studies a majority of which found PCV13 adult to be cost-effective but all of which were hampered by not having access to the important CAPITA trial estimates of vaccine efficacy. A more recent review by Treskova et al (2019) 18 stratifies the newer literature according to assumptions about herd effects from pediatric vaccination (i.e., whether effects were ongoing or completed, whether effects were from pediatric PCV13 (PCV13 Pediatric) or from pediatric 10-valent pneumococcal conjugate vaccine (PCV10 Pediatric), or whether there was a switch in pediatric vaccination from PCV10 to PCV13 or vice versa), and according to the policy being evaluated (PPV23 versus no vaccination, PCV13 versus no vaccination, and adding PCV13 to PPV23). Of the four studies that evaluate the addition of PCV13 Adult to adult PPV23 (as was the case in Turkey), van Hoek and Miller (2016), 20 Blommaert et al (2016), 21 and Willem et al (2018) 22 found doing so to be cost-ineffective, while Stoecker et al (2016) 23 found it to be cost-effective only in the short run before herd effects fully set in.…”
Section: Literature On Economic Evaluation Of Pcv13 Adultmentioning
confidence: 99%
See 1 more Smart Citation
“…The model also accounted for the vaccine effect waning in the base case. It was assumed that vaccinated children received the full benefit of the vaccine (i.e., no waning effectiveness) during the first five years after vaccination and then the VE decreased linearly to 0% over the next 10 years (i.e., from Year 6 to Year 15 after the last vaccine dose) [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the dynamic transmission model, the force of infectivity can change over time due to changes in the size of the susceptible population. A recent systematic review paper [78] of cost-effectiveness analysis publications for adult PCV13 included only static models. The dynamic transmission model requires more data on the transmission aspects and this data is scarce, which leads to many assumptions.…”
Section: Sensitivity Analysismentioning
confidence: 99%